Contextualizing EFL Listening through AI: A Study on Perception of Students and Teacher - Novita Andini; Dedi Irwan; Rahayu Meliasari (CV. AFDIFAL MAJU BERKAH, 2026)
This research aims to examine students’ and teacher’s perceptions of the use of Generative Artificial Intelligence (GenAI) tools specifically ChatGPT and Google AI Studio in context-based English language learning. This study employs a qualitative descriptive design. The participants consisted of two female students, one male student, and an English teacher from a senior high school in Pontianak. Data were collected through semi-structured interviews and non-participant observation, then analyzed using thematic analysis. The research findings regarding student perceptions indicate that GenAI-based listening materials enhance student engagement and motivation because they are more relevant to their daily lives. Students also found it easier to understand the material, remember vocabulary, and felt more confident in their learning. From the teacher’s perspective, GenAI helps in creating learning materials more efficiently and contextually. However, there are several challenges, such as infrastructure limitations and the need to improve teacher’s competencies in using technology. Overall, the use of GenAI in contextual listening instruction has a positive impact on the learning process, although it still requires further development and support for optimal implementation